Signaling of exercise stimuli: mitochondria as communicators - Burtscher, Johannes (Current Issues in Sport Science (CISS), 2023)
Regular exercise exerts a number of beneficial systemic effects and is associated with better health and performance as well as with reduced vulnerability and mortality from many diseases. While the working muscles are immediately affected by physical and biochemical consequences of physical activity, it is less well understood, how exercise-stimuli can lead to benefits in distant tissues and organs. Various modes of inter-tissue communication are likely involved and include physical-activity related systemic temperature and metabolic changes but also circulating signaling molecules, sometimes refered to as “exerkines”.We are particularly interested in a subgroup of these signaling molecules, namely those that are induced by mitochondrial stress and communicate such stimuli to remote organs, effecting mitochondrial changes there. This group of molecules is termed mitokines and includes peptides that are expressed in the nucleus, such as FGF21 and GDF15, and mitochondria-derived peptides, notably humanin. Mitokines are likely important contributors to beneficial exercise effects to organs such as the brain, heart or lung and therefore are involved in the well-acknowledged physical activity-induced protection from neurological, cardio-vascular diseases and pulmonary diseases.The activation of mitokine-signaling requires mitochondrial stress, which in healthy organisms is usually met with the induction of adaptive mechanisms that bolster cellular resilience, for example by an improving the efficiency of anti-oxidant and anti-inflammatory defense mechanisms. Such adaptations are thought to be protective factors in many diseases from which regular exercise can protect. Mitochondrial stress, however, can also be detrimental under certain conditions and especially, if the stress exceeds the adaptive capacities of the system (cell, tissue, organ or organism) or, if the resilience of the system is compromised, for example due to disease, fatigue or insufficient regeneration time from previous stressors. The concept of such bi-phasic responses is termed hormesis and means that mild stress is met by beneficial adaptations and protections but severe stress has long-term detrimental consequences.The aim of this contribution is to present the evidence that mitochondrial stress due to exercising skeletal muscle leads to the release of mitokines, which in turn modulate mitochondrial quality control, dynamics, antioxidative capacities and respirational activity in a selection of target organs (with a focus on brain and lung). According to the hormetic principle, exercise improves the health of these organs. However, in some cases, mitochondrial communication may be involved in adverse effects of exercise, which will be discussed using the example of heart-kidney mitochondrial crosstalk.